Republic of Mozambique : First Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria-Staff Report; Press Release. (IMF Staff Country Reports; Country Report, 2014)
The Executive Board of the IMF has completed the first review under the three-year Policy Support Instrument (PSI) for Mozambique. Mozambique's macroeconomic performance remains strong: real GDP growth for 2013 is estimated at 7.1 percent and inflation remains moderate. The PSI-supported program is broadly on track. Structural reforms along a broad policy spectrum should be implemented vigorously to foster sustained and more inclusive growth. With foreign aid likely to decline over the medium term, increased nonconcessional borrowing can provide additional resources for improving physical infrastructure and human capital. Further strengthening debt management and investment planning and implementation are essential to ensure value for money, maximize the efficiency of investment, and preserve debt sustainability.